2018
DOI: 10.4183/aeb.2018.466
|View full text |Cite
|
Sign up to set email alerts
|

The effects of Opium Addiction on Thyroid and Sex Hormones in Diabetic and Non-Diabetic Male and Female Rats

Abstract: Objective. Opium is a narcotic drug that is commonly abused. The prescription of pharmaceutical derivatives of opium is limited due to their possible harmful effects on the body's metabolism and tolerability by patients. The aim of the present study was to evaluate the effects of chronic opium consumption on some sexual and thyroid hormones in diabetic and non-diabetic male and female rats.Material and Methods. This experimental study was conducted on 56 Wistar rats. The animals were divided into diabetic addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Drug-induced hypersecretion caused by dopamine receptor blocking agents, dopamine depleting agents, histamine receptor antagonist, estrogens, anti-androgens, serotonin reuptake inhibitors, and calcium channel blockers 79 83…”
Section: Causes Of Hyperprolactinemiamentioning
confidence: 99%
“…Drug-induced hypersecretion caused by dopamine receptor blocking agents, dopamine depleting agents, histamine receptor antagonist, estrogens, anti-androgens, serotonin reuptake inhibitors, and calcium channel blockers 79 83…”
Section: Causes Of Hyperprolactinemiamentioning
confidence: 99%
“…Recently, the World Health Organization (WHO) reported that among Islamic countries, Iran has the highest rate of opioids abuse [ 19 ]. Animal studies suggest that consumption of narcotics results in thyroid dysfunction [ 20 , 21 ]. Besides, in some trials, diminished T3 uptake has been shown in opium abusers [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the World Health Organization (WHO) reported that among Islamic countries, Iran has the highest rate of opium abuse [19]. Studies on rodent models suggest that consumption of narcotics (opium and morphine) results in the dysregulation of THs [20,21]. Besides, in some trials, diminished T3 uptake has been shown in opium abusers [22].…”
Section: Introductionmentioning
confidence: 99%